2020
DOI: 10.1111/jch.13833
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular strain and arterial hypertension: Is longitudinal strain ready for primetime?

Abstract: More than one decade passed from the first studies regarding left ventricular (LV) mechanics in patients with arterial hypertension (AH). At the beginning, the assessment of LV strain was considered as a research tool, which was exclusively used in well-equipped echocardiographic laboratories. What is the situation nowadays and does LV strain still has status of "fancy gadget" or necessity in the evaluation of subclinical subtle cardiac damage in patients with AH?The first studies used tissue-Doppler derived L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…This is in accordance with findings of a recent meta-analysis that found consistently lower systolic and diastolic BP after MICT than HIIT training (35). Whether this is causally related to the decline in GLS observed in the HIIT group remains to be established (36). A possible explanation for higher BP values after HIIT could be increased sympathetic activity.…”
Section: Left Ventricular Geometry and Functionsupporting
confidence: 91%
“…This is in accordance with findings of a recent meta-analysis that found consistently lower systolic and diastolic BP after MICT than HIIT training (35). Whether this is causally related to the decline in GLS observed in the HIIT group remains to be established (36). A possible explanation for higher BP values after HIIT could be increased sympathetic activity.…”
Section: Left Ventricular Geometry and Functionsupporting
confidence: 91%
“…[37][38][39][40][41][42] Conversely, LV circumferential performance deteriorates in more advanced stages of the disease, and may even increase the asymptomatic phase of heart failure (stage B) to compensate for the dysfunction in the longitudinal direction. 10,[43][44][45][46][47][48] This paper demonstrated that changes in LV longitudinal systolic deformation over follow-up were associated with alterations in relevant LV afterload-associated indices, among which central augmentation pressure remained an independent predictor after multivariable adjustments for possible confounders. Similar to GLS, the independent contribution from central augmentation pressure parameters was evident for LV circumferential strain as well.…”
Section: Discussionmentioning
confidence: 67%
“…GLS can serve as a marker of early stage of myocardial damage. It was confirmed that LV mechanics and primarily longitudinal strain is impaired in patients with arterial hypertension [48]. Assessment of GLS can thus unmask systolic dysfunction, which is undetected by conventional ejection fraction in uncomplicated hypertension [49].…”
Section: Discussionmentioning
confidence: 89%